The Battle of Britain Experience - Overy, Richard (London Sevenoaks, 2010)
On 18th June 1940, Churchill declared in the House of Commons - "The Battle of France is over... the Battle for Britain is about to begin". In July, Hitler told his commanders to prepare for the invasion of England. To do this they would have to destroy the RAF - Britain's last line of defence. This book deals with this topic
Include Color Illustration and Index
Keywords: World War (1939-1945) -- Great Britain -- Military operations, Aerial--British